(untitled) (Research, Society and Development, 2025)
This article aims to describe how the order of presentation of items in nominal scales influences decision making at the time of choice. By applying a survey and collecting data through a questionnaire self-completed by 800 students in public schools, a database was created. To identify the order and primacy and recency effect was applied a specific questionnaire with inverse sequential allocation of items in the same sample group. To identify the order and primacy and recency effect was applied a specific questionnaire in an parallel test with inverse sequential allocation of items in the same sample group. In order to measure decision-making under different circumstances, a questionnaire with random ordering of items was applied to an experimental group. To measure the influence of order on dichotomous scales, a presentation in standard mode and another in reverse mode was applied to an experimental group using the split half method. The results show that there is a tendency to choose the first items presented or the primacy effect. However, the choice of items is a combination of several influences, such as question and item content, psycholinguistic aspects of the items, specific framing, interval of the survey application in relation to parallel test, type of scale such as dichotomous or polyatomic, etc., which makes it difficult to identify clearly the influence of order or primacy or recency effect.